2010
DOI: 10.1002/mds.23148
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind, placebo‐controlled study to assess the mitochondria‐targeted antioxidant MitoQ as a disease‐modifying therapy in Parkinson's disease

Abstract: Multiple lines of evidence point to mitochondrial oxidative stress as a potential pathogenic cause for Parkinson's disease (PD). MitoQ is a powerful mitochondrial antioxidant. It is absorbed orally and concentrates within mitochondria where it has been shown to protect against oxidative damage. We enrolled 128 newly diagnosed untreated patients with PD in a double-blind study of two doses of MitoQ compared with placebo to explore the hypothesis that, over 12 months, MitoQ would slow the progression of PD as me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
341
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 510 publications
(350 citation statements)
references
References 31 publications
5
341
1
3
Order By: Relevance
“…However, the relevance of such studies to the human condition remains uncertain, because acute neurotoxins are rarely the culprit in the majority of PD cases. This potential discrepancy is highlighted by a number of failed clinical trials that have heavily relied on toxin models as preclinical evidence for efficacy (13)(14)(15)(16). A more representative model of DA loss that uses known factors in human PD is likely vital to develop better therapeutic outcomes.…”
mentioning
confidence: 99%
“…However, the relevance of such studies to the human condition remains uncertain, because acute neurotoxins are rarely the culprit in the majority of PD cases. This potential discrepancy is highlighted by a number of failed clinical trials that have heavily relied on toxin models as preclinical evidence for efficacy (13)(14)(15)(16). A more representative model of DA loss that uses known factors in human PD is likely vital to develop better therapeutic outcomes.…”
mentioning
confidence: 99%
“…To date, the utilities of a therapeutic strategy using MitoQ have been demonstrated in in vivo experiments using various disease model animals [15,[34][35][36]. Moreover, MitoQ has been investigated in clinical trials [20,37,38] and is expected to be promising candidate for a mitochondrial medicine. MitoQ was also investigated for protection of the liver and heart from I/R injury in in vivo experiments using I/R injury induced mice and rats [15,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that targeting CoQ 10 to mitochondria by mitoquinone, designed based on the premises that offsetting mitochondria-generated oxidative stress will protect dopaminergic neurons did not achieve this goal. A clinical trial involving 128 newly diagnosed PD patients receiving either 40 or 80 mg/day mitoquinone for over 12 months failed to slow the progression of PD as measured by the Unified Parkinson's Disease Rating Scale (Snow et al, 2010).…”
Section: Discussionmentioning
confidence: 99%